2008
DOI: 10.1177/0310057x0803600113
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effect of Total Intravenous Anaesthesia with Propofol and Remifentanil and Inhalational Anaesthesia with Isoflurane on the Release of Pro- and Anti-Inflammatory Cytokines in Patients Undergoing Open Cholecystectomy

Abstract: The aim of the study was to investigate the effects of two anaesthetic techniques (total intravenous technique vs. inhalational technique) on changes in pro-and anti-inflammatory cytokine levels during open cholecystectomy. Forty ASA PS I-II patients undergoing open cholecystectomy were randomly assigned to two groups. Group R received total intravenous anaesthesia with propofol and remifentanil and group F received balanced inhalational anaesthesia with isoflurane. The plasma levels of tumour necrosis factor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 29 publications
(29 reference statements)
4
53
1
4
Order By: Relevance
“…Our findings are in agreement with previous studies showing that the greatest increase in plasma interleukins IL-6 and IL-10 occur in the first 2 to 4 h after surgery and diminish during the subsequent 24 h. [29][30][31][32] In a study similar to ours, El Azab et al 25 It is difficult to compare different studies of the effect of dexamethasone on cytokine balance during different surgical procedures because of different doses and study protocols. 16,18 The influence of anaesthetic agents must also to be taken into consideration.…”
Section: Resultssupporting
confidence: 92%
“…Our findings are in agreement with previous studies showing that the greatest increase in plasma interleukins IL-6 and IL-10 occur in the first 2 to 4 h after surgery and diminish during the subsequent 24 h. [29][30][31][32] In a study similar to ours, El Azab et al 25 It is difficult to compare different studies of the effect of dexamethasone on cytokine balance during different surgical procedures because of different doses and study protocols. 16,18 The influence of anaesthetic agents must also to be taken into consideration.…”
Section: Resultssupporting
confidence: 92%
“…53 A possible reason for this is that intravenous GA, when compared to volatile GA has been shown to increase IL-10, which is known to have antitumor activity and help with healing and repair. 15,54 Epidural anesthesia in combination with GA, compared to GA alone, has been shown to increase the ratio of Th1 cells to Th2 cells in patients with hepatocellular carcinoma, potentially promoting antitumor activity. 55 The Th1⁄Th2 ratio has also been shown to decrease after volatile GA, whereas propofol did not induce any change.…”
Section: Effect Of Anesthetic Choice On Anticancer Immunitymentioning
confidence: 99%
“…63 Of interest, propofol did not exhibit these effects; instead, propofol seems to have protective effects through various mechanisms, including inhibition of COX-2, 65 inhibition of PGE 2 , but also through enhancement of antitumor immunity. 66 Ke et al 67 showed in patients undergoing open cholecystectomy that the combination of propofol and remifentanil resulted in an increase in antiinflammatory cytokines IL-10 (known to have antitumor activity and help with healing and repair), as compared with inhaled anesthesia with isoflurane. Inada et al 68 found in patients undergoing supratentorial tumor excision that propofol anesthesia mitigated the adverse effects of surgical stress-induced immune response better than isoflurane.…”
Section: Anesthetic Induction Drugs and Volatile Anestheticsmentioning
confidence: 99%